Trusted Chief Executives in Convenient White-Collar Crime - Gottschalk, Petter (Crime & delinquency, 2025)
Convenience exists in the financial motive, the organizational opportunity, and the personal willingness for deviant behavior. These three themes can result in 14 convenience propositions as presented in this article. In cases where an offender is detected, the offense can be examined by identifying relevant convenience issues in the structural model of crime convenience. Not all of the 14 issues will be relevant to create a narrative of one specific incident. In cases where prevention of offenses is the issue, then vulnerability review is appropriate for all 14 propositions. For example, domination of greed or extensive differential association can signal strong motivation or strong willingness for wrongdoing, while lack of oversight and guardianship can signal an invitation for wrongdoing.